2019
DOI: 10.3390/nu11030562
|View full text |Cite
|
Sign up to set email alerts
|

“The One Time You Have Control over What They Eat”: A Qualitative Exploration of Mothers’ Practices to Establish Healthy Eating Behaviours during Weaning

Abstract: Background: Weaning marks the transition from a milk-only diet to the consumption of solid foods. It is a time period where nutrition holds an undeniable importance and taste experiences have a long-lasting effect on food preferences. The factors and conditions that form parental feeding practices are yet to be fully understood; doing so can help target problematic behaviours and develop interventions aiming to modify them. Objective: This study used a qualitative methodology to gain a better understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…Parents intended to create positive structures and routines but were often challenged by time, cost, competing priorities, and other external influences, such as marketing and peer pressure. This is consistent with research that has shown the variety of external factors that can influence parents’ feeding practices [ 16 , 30 , 38 , 47 , 48 ]. Education and support that address family and cultural priorities, and that empower parents by providing strategies and building confidence to overcome external influences while also preventing or addressing internalized feelings of shame or guilt can be beneficial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Parents intended to create positive structures and routines but were often challenged by time, cost, competing priorities, and other external influences, such as marketing and peer pressure. This is consistent with research that has shown the variety of external factors that can influence parents’ feeding practices [ 16 , 30 , 38 , 47 , 48 ]. Education and support that address family and cultural priorities, and that empower parents by providing strategies and building confidence to overcome external influences while also preventing or addressing internalized feelings of shame or guilt can be beneficial.…”
Section: Discussionsupporting
confidence: 91%
“…For example, just under half of the participants in this study indicated they infrequently introduced new foods to their child. Limited time is a pressure that can result in authoritarian feeding practices that override strategies to develop autonomy [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actual and perceived health properties of the food. Providing a healthy diet was voiced as a priority in most studies that addressed the choice of complementary foods (26,31,(33)(34)(35)(37)(38)(39)(40)(41)(43)(44)(45)(46)48,50,(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64) . Parents shared a desire to provide a balanced diet with foods from all groups that will secure a sufficient intake of nutrients.…”
Section: Factors Related To Type Of Complementary Foodsmentioning
confidence: 99%
“…Nutrition during the first 1000 days, spanning from conception to age 24 months, has critical influence on the immediate and long-term physical and cognitive development of infants. The period from birth through the first 12 months characterizes a unique time when parents or caregivers make essentially all feeding decisions about what and how their infant is offered food [1]. Although the definition of a modern family is changing [2], parents are currently described as the main caregivers of children in the home [3] and infant feeding is a large component of that care that encompasses the social, cultural, and economic structure of a parent's life [4].…”
Section: Introductionmentioning
confidence: 99%